Modulation of type beta transforming growth factor activity in bone cultures by osteotropic hormones. - Pfeilschifter, J (1987)
Type beta transforming growth factor (TGF-beta) activity was found in conditioned medium harvested from fetal rat and neonatal mouse calvariae by using the anchorage-independent growth of normal rat kidney fibroblasts as an indicator system. Calvariae incubated with parathyroid hormone, 1,25-dihydroxyvitamin D3, and interleukin 1, all factors that stimulate bone resorption showed a concentration-dependent increase in TGF-beta activity in the culture medium. Increases in TGF-beta activity persisted undiminished for 48 hr after removal of these factors. The increases in TGF-beta activity from the resorbing bone cultures were relatively greater than the increases in bone resorption. Calcitonin inhibition of bone resorption correlated with a decrease in TGF-beta activity. Thus, agents that modulate bone resorption also affect TGF-beta activity in the bone culture medium. Changes in local concentrations of TGF-beta activity by osteotropic hormones may be important in the regulation of normal bone remodeling.